2020
DOI: 10.1039/d0fo01899f
|View full text |Cite
|
Sign up to set email alerts
|

Velvet antler polypeptide prevents the disruption of hepatic tight junctionsviainhibiting oxidative stress in cholestatic mice and liver cell lines

Abstract: The aim of the present study was to examine the protective effects and mechanism of velvet antler polypeptide (VAP) against lithocholic acid (LCA)-induced cholestatic liver injury in mice. A 7.0...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Most O 2 · − is dismutated by MnSOD to form H 2 O 2 in mitochondria [ 8 ]. Subsequently, mitochondrial H 2 O 2 diffuses into the cytoplasm to enhance oxidative damage, which is presumed to exert critical effects on the development of liver diseases, including hepatic steatosis, cholestatic liver injury and liver fibrosis [ 4 , 29 , 30 ]. Based on accumulating evidence, H 2 O 2 induces ECM synthesis by directly promoting collagen gene transcription in activated HSCs [ 31 , 32 ], which suggests that interventions designed to reduce mitochondrial H 2 O 2 production might be effective strategies for preventing liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most O 2 · − is dismutated by MnSOD to form H 2 O 2 in mitochondria [ 8 ]. Subsequently, mitochondrial H 2 O 2 diffuses into the cytoplasm to enhance oxidative damage, which is presumed to exert critical effects on the development of liver diseases, including hepatic steatosis, cholestatic liver injury and liver fibrosis [ 4 , 29 , 30 ]. Based on accumulating evidence, H 2 O 2 induces ECM synthesis by directly promoting collagen gene transcription in activated HSCs [ 31 , 32 ], which suggests that interventions designed to reduce mitochondrial H 2 O 2 production might be effective strategies for preventing liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-accepted that the hepatic tight junction is involved in various processes of liver diseases. The hepatic tight junction, involving occludin and claudin-1 and ZO-1, serves as a barrier to keep bile away from the blood circulation on hepatocytes . Also, the liver–gut–liver circulation of bile acid is critical for the absorption of nutrients and the regulation of metabolism …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CES has shown antioxidant effects in murine models of obesity, rheumatoid arthritis, fatty liver, and nephrotoxicity [ 11 , 20 , 21 , 22 ], and previous studies, particularly those focusing on neurological disease, have reported that the methanol extracts of velvet antler ameliorate Parkinson’s disease by inhibiting oxidative stress and neuroinflammation [ 18 ]. Although these results were demonstrated in neuronal-like cell lines and various disease models, neurotherapeutic effects have not been directly observed in mature neurons.…”
Section: Introductionmentioning
confidence: 99%